Cybersecurity Improvement Design in Critical Infrastructure PT XYZ Case Study - Rizal Fathoni Aji; Gunawan, Adi (The Indonesian Journal of Computer Science, 2023)
Prevention of cyber attacks is an important factor that organizations need to do to support maximum business process continuity. One of the important factors needed is the protection of data and information assets by the critical infrastructure owned. This paper discusses increasing the capacity of critical infrastructure at XYZ organization. The NIST CSF framework is a benchmark assessment tool for critical infrastructure capacity at PT XYZ. The results obtained from the assessment are used to make recommendations for controls related to critical infrastructure. The risk assessment found 107 risk scenarios that led to 11 recommendations for critical infrastructure improvement areas. Prioritization of the resulting recommendations is expected to increase the resilience and capacity of critical infrastructure at PT XYZ in the face of current and future cyber threats.